Handbook of fertility : nutrition, diet, lifestyle and reproductive health - Watson, Ronald R. (Ronald Ross) (Elsevier : Academic Press, 2015)
Handbook of Fertility: Nutrition, Diet, Lifestyle and Reproductive Health focuses on the ways in which food, dietary supplements, and toxic agents, including alcohol and nicotine affect the reproductive health of both women and men. Researchers in nutrition, diet, epidemiology, and endocrinology will find this comprehensive resource invaluable in their long-term goal of understanding and improving reproductive health. This book brings together a broad range of experts researching the different aspects of foods and dietary supplements that promote or detract from reproductive health.